Unmasking Media Narratives through Comparative Corpus Linguistic Analysis: A Study of Russia-Ukraine Conflict - Obaidullah, Md.; Shaikh, Hasan (English Department of Faculty of Tarbiyah and Teacher Training, 2024)
In a world inundated with diverse media narratives, the Russia-Ukraine conflict emerges as a focal point of contention, revealing a complex interplay of linguistic strategies and discursive tactics. This study aims to unravel the intricacies of lexical choices, and discursive techniques employed by Sputnik, BBC, and Fox News in their coverage of the Russia-Ukraine conflict through corpus-assisted discourse studies techniques. Three corpora were created comprising 5,347 articles with 5,829,747 tokens, sampled from February 2022 to February 2023. Moreover, Sputnik’s diction strategically employs the phrase “military operation” while eschewing “war”, portraying the conflict as a defensive, legitimate endeavour, thus reinforcing a Russian geopolitical narrative that recasts Ukraine not as a victim but as an active participant with extremist factions. BBC, in contrast, adopts a pro-Western stance, framing Ukraine as a victim and Russia as an aggressor. Fox News calls Russia’s action as an invasion, and highlights the individual roles of political leaders in shaping the conflict. However, to address the limitations of this study, future studies can expand the scope, sources, languages, and genres for analysis. Furthermore, media consumers need to practice media literacy, cross-checking, and critical analysis in the era of overloaded information in order to form well-rounded opinions on complex geopolitical events.